2016
DOI: 10.1016/j.cjtee.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pediatric femoral shaft fractures by stainless steel and titanium elastic nail system: A randomized comparative trial

Abstract: PurposeLiterature suggests that the lower modulus of elasticity of titanium makes it ideal for use in children compared with stainless steel. Better fracture stability was observed in association with titanium nails on torsional and axial compression testing. However, stainless steel nails are stiffer than titanium counterparts, which may provide a rigid construct when fixing paediatric femoral shaft fractures. Complications have been observed more frequently by various researchers when titanium nails are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
(14 reference statements)
1
15
1
Order By: Relevance
“…The study found that the conventional plate fixation treatment had characteristics of longer length of surgical incision and more intraoperative bleeding although it was effective, and it had a negative impact on the prognosis of children due to the poor compliance of children. Compared with the conventional plate fixation, internal fixation of elastic stable intramedullary nail has favourable elastic restoring force as its main material is titanium alloy, which is more helpful to the stability after fracture reduction and has a positive effect for the recovery of physiological curvature of shaft of femur 17,18. Moreover it can resist the tension, pressure and rotating force at the fracture site, which is more conductive to generation of callus and can promote the early healing of fracture 19…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the conventional plate fixation treatment had characteristics of longer length of surgical incision and more intraoperative bleeding although it was effective, and it had a negative impact on the prognosis of children due to the poor compliance of children. Compared with the conventional plate fixation, internal fixation of elastic stable intramedullary nail has favourable elastic restoring force as its main material is titanium alloy, which is more helpful to the stability after fracture reduction and has a positive effect for the recovery of physiological curvature of shaft of femur 17,18. Moreover it can resist the tension, pressure and rotating force at the fracture site, which is more conductive to generation of callus and can promote the early healing of fracture 19…”
Section: Discussionmentioning
confidence: 99%
“…53 However, metals are nonbiodegradable, which may produce unwanted biohazardous tip waste induced by the broken MNs left behind in the skin, even though some metals, such as SS and Ti, have been safely used as biomaterials in medical treatment for decades. 121,122…”
Section: Classification Of Mnsmentioning
confidence: 99%
“…53 However, metals are nonbiodegradable, which may produce unwanted biohazardous tip waste induced by the broken MNs left behind in the skin, even though some metals, such as SS and Ti, have been safely used as biomaterials in medical treatment for decades. 121,122 Polymer. Nowadays, polymeric MNs have attracted great attention of researchers because most polymeric MNs are biocompatible and biodegradable to avoid harsh side effects in the skin, providing a safe device for the delivery of drugs.…”
Section: Classified By Materials Of Mnsmentioning
confidence: 99%
“…The majority of the paediatric femoral shaft fractures are now treated operatively, with economic and social benefits over conservative treatment [7]. Surgical treatment by using titanium elastic nailing (TEN) proved its efficacy when referring to hospitalization period, duration until assistive or independent walking, and returning to school [8].…”
Section: Introductionmentioning
confidence: 99%